2017
DOI: 10.1080/14992027.2017.1346304
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre study evaluating the effects of the Swedish ACE programme

Abstract: The ACE programme is effective, is recommended for implementation in clinical settings and is considered an alternative or additional treatment to hearing aid rehabilitation. Additional studies that include younger individuals and a control group are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
(26 reference statements)
3
22
1
1
Order By: Relevance
“…These qualitative analyses showed that individuals appreciate meeting in groups and sharing experiences to learn more about hearing impairment and how to use different communication strategies. The participants stated that they had increased their ability to deal with hearing loss, and they reported that they had become more open about telling others about their hearing loss ( € Oberg 2017; € Oberg, Bohn, and Larsson 2014a;€ Oberg et al 2014b). These qualitative aspects are in line with the findings by Southall et al (2018), who found that group rehabilitation provided better awareness of hearing loss and that increased social belonging led to personal transformation.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…These qualitative analyses showed that individuals appreciate meeting in groups and sharing experiences to learn more about hearing impairment and how to use different communication strategies. The participants stated that they had increased their ability to deal with hearing loss, and they reported that they had become more open about telling others about their hearing loss ( € Oberg 2017; € Oberg, Bohn, and Larsson 2014a;€ Oberg et al 2014b). These qualitative aspects are in line with the findings by Southall et al (2018), who found that group rehabilitation provided better awareness of hearing loss and that increased social belonging led to personal transformation.…”
Section: Introductionsupporting
confidence: 77%
“…Between 2013 and 2014, 83 individuals in the four regions participated in the evaluation of the ACE course ( € Oberg 2017). Of these, 81 were eligible to participate in the validation of the questionnaire.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that both individual and group auditory rehabilitation interventions can effectively increase communication strategy use [ 22 , 31 , 33 , 60 ] both in the short- and long term. A plausible explanation for the absence of an effect in this study may be related to the video-watching rates as reported in our process evaluation study (submitted).…”
Section: Discussionmentioning
confidence: 99%